The Dynamic of Power Relationship in Judges 16:1- 22 and Its Relevance in the Indonesian Context - Juliana A Tuasela (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2022)
Judges 16:1 – 22 prominently present a dynamic power relationship between the characters in the particular narrative of Samson, Delilah, the Philistines, and YHWH. This article aims to explore a number of tendentious and dynamic power relations in this text using the method of interpreting narrative criticism. From the perspective of narrative criticism, the text of Judges 16:1-22 was a dramatic story between Samson and Delilah that was interpretable. This text elaborated every element of the story, whether plot, setting, time and character, into a dramatic and meaningful narrative. The interpretation of this text was studied by searching gaps in the story as well as between actors and bridging them with discursive studies. Because sometimes the interpreter ignored the gap in the narrative as an important part of the narrative interpretation. If the story gap was interpreted critically, it produces and constructs powerful theological values. The identification of this story gap was initiated by conducting a structural analysis of the text. The results of this exegesis would be able to form a theological value formulation that had relevance in the current context. The author tried to dialogue the theological values in the narrative of Judges 16:1-22 with contextual realities in Indonesia.